Search for Charged Massive Long-Lived Particles - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alimena, J.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Sawyer, L.; et al. (Amer Physical Soc, 2012)
We report on a search for charged massive long-lived particles (CMLLPs), based on 5.2 fb(-1) of integrated luminosity collected with the D0 detector at the Fermilab Tevatron p (p) over bar collider. We search for events in which one or more particles are reconstructed as muons but have speed and ionization energy loss (dE/dx) inconsistent with muons produced in beam collisions. CMLLPs are predicted in several theories of physics beyond the standard model. We exclude pair-produced long-lived gauginolike charginos below 267 GeV and Higgsino-like charginos below 217 GeV at 95% C.L., as well as long-lived scalar top quarks with mass below 285 GeV.